Can machine learning save children at risk?. Issue 6 (21st November 2022) - Sanders, Michael; Clayton, Vicky
Abstract : The idea that machine learning can improve children's social care is attractive, but fraught with challenges – the veil of secrecy around predictive analytics in public services must be lifted, say Michael Sanders and Vicky Clayton Abstract : The idea that machine learning can improve children's social care is attractive, but fraught with challenges – the veil of secrecy around predictive analytics in public services must be lifted, say Michael Sanders and Vicky Clayton